Searching for the holy grail – excellent staff and carers who work with children - Kate Skinner (Scottish Journal of Residential Child Care)
Since Utting's report, Children in the Public Care (1991), Warner's seminal report, Choosing with Care (1992) in England and Wales, and Another Kind of Home (Skinner, 1992) in Scotland, social work managers responsible for recruiting and selecting staff and carers who work with children have been exhorted to improve the methods they use. However, a quick glance around Scotland today would show that since the early nineties not much has changed. The reasons for the relatively low level of change are many, but the imperatives from reports, inquiries and more general literature (Gulbenkian Foundation, 1993; Cullen, 1996; Social Work Services Inspectorate, 1997; Marshall et al, 1999; Waterhouse, 2000) have combined to signal one consistent message: transformational change is needed in the difficult process of selecting staff and carers who work with children.